The effect of the dissolution process and the polyaniline content on the properties of polyacrylonitrile–polyaniline composite nanoweb - Kizildag, Nuray; Ucar, Nuray; Karacan, Ismail; Onen, Aysen; Demirsoy, Nesrin (SAGE Publications, 2014)
There are several studies regarding polyacrylonitrile composite nanofibers with polyaniline doped with dodecylbenzene sulfonic acid and solved by N,N′-dimethyl formamide which were mostly performed to analyze the thermal and morphological properties. In this study, camphor sulfonic acid-doped polyaniline and polyacrylonitrile composite nanofibers were electrospun from solutions in dimethylsulfoxide and the effect of polyaniline content and the application of different dissolution methods on the morphology, chemical structure, conductivity, crystallinity, mechanical, and thermal properties of nanowebs were investigated. Morphology, nanofiber diameters, chemical structure, crystallinity, mechanical properties, and thermal properties of the nanofibers were all affected by the polyaniline addition. Compared to the conductivity of neat polyacrylonitrile nanofibers, the conductivity of the composite nanofibers was improved, reaching a value higher than 10−6 S/cm with 3 wt% polyaniline content which was in the range for electrostatic discharge applications (10−9 to 10−6 S/cm). Increase in dissolution time and application of ultrasonic homogenization affected the diameter, mechanical properties, crystallinity, and thermal properties of the nanofibers, while they had negligible effects on conductivity.